Digital Literacy As A Media Guide Amid Digital Disruption (Study of The Importance of Digital Literacy in The Era of Globalization) - Syaifudin Zuhri; Rozaqul Arif (Publikasi Indonesia, 2024)
The rapid development of information and communication technology (ICT) in the last 15 years has made people aware of digital technology is importance in life. However, the impact of this technology has created an